PENGARUH FAKTOR INTERNAL BANK DAN SERTIFIKAT BANK INDONESIA TERHADAP PENYALURAN KREDIT PERBANKAN DI INDONESIA - Putri Pratista Nugraheni; Wahyu Meirantoo (Diponegoro Journal of Accounting, 2013)
This research was aimed to examine the effect of bank internal factors and certificates of Bank Indonesia to bank loan in Indonesia. Bank internal factors are measured by third party found (DPK), capital adequacy ratio (CAR), loan to deposit ratio (LDR), return on assets (ROA), and non performing loan (NPL). The population in this research is all of banking companies that listed in Indonesian Stock Exchange (IDX) in 2009-2012. Samples are collected by purposive sampling method and in this research multiple linear regression analysis is used as analysis method. The result of this research proved that third party fund and capital adequacy ratio had significantly positive effects to bank loan. Meanwhile, loan to deposit ratio, return on assets, and certificates of Bank Indonesia had positive but not significant effects to bank loan, and non performing loan has significantly negative effect to bank loan.